Humanising medicine: teaching on tri-morbidity using expert patient narratives in medical education. Issue 6 (2nd November 2019) - Player, Emily; Gure-Klinke, Heidi; North, Sophie; Hanson, Sarah; Lane, Donald; Culyer, Graham; Rodrigues, Veena
ABSTRACT: Expert patients have recognised benefits for both students and patients in medical education. However, marginalised patients such as homeless patients are less likely to participate. Learning from such individuals is crucial for future doctors, who can, in turn, aid their inclusion in society and improve access to health care. A 'humanising medicine' lecture was delivered to Year Four medical students at Norwich Medical School. The lecture utilised narratives from patients with experience of homelessness and tri-morbidity (physical and mental health problems and substance abuse). We used a qualitative approach to evaluate this teaching and understand the experience of both students and patients. Students were asked to complete questionnaires, whereas expert patients were interviewed. We thematically analysed data using an inductive approach. Students reported an increased understanding, empathy and preparedness to consult with marginalised patients. Expert patients described positive feelings about their involvement, giving something back, and the therapeutic benefits of telling their story. We found that including marginalised patients in medical education had positive benefits for both students and patients. Our findings suggest that expert patient narratives are valuable in medical education particularly in teaching and learning about medical complexity and tri-morbidity.